Direct deposition of anatase TiO2 on thermally unstable gold nanobipyramid: Morphology-conserved plasmonic nanohybrid for combinational photothermal and photocatalytic cancer therapy - Jang, Dohyub; Yu Subin; Chung Kyungwha; Yoo Joung Hyun; Mota Filipe Marques; Wang Jianfang; Ahn Dong June; Kim Sehoon; Ha Kim Dong (Elsevier BV, 2022)
Deposition of crystalline titanium dioxide (TiO2) on gold nanostructures has been considered as a promising strategy for near-infrared (NIR) light-activated photocatalysis. A typical route comprises pre -deposition of amorphous TiO(2 )on the gold surface and its ensuing crystallization by high-temperature annealing. Such condition, however, is not compatible with highly plasmonic but thermally unstable sharp-tipped gold nanostructures, causing structural disruption and plasmonic decline. Herein, we report a hybridization method excluding high-temperature annealing, i.e., direct deposition of anatase TiO(2 )onto sharp-tipped gold nanobipyramid (Au NBP/a-TiO2) with conserving their morphology without agglomeration via low-temperature hydrothermal reaction. In addition to keeping the plasmonic photothermal performance, Au NBP/a-TiO(2 )exhibits enhanced photocatalytic generation of reactive oxygen species in response to the NIR excitation, evidencing the efficient injection of hot electrons from the Au NBP to the anatase shell. In vitro and in vivo studies revealed that the efficient photocatalytic/photothermal responses of Au NBP/a-TiO2, along with dispersion stability in biological media and minimal toxicity, hold potential for synergistic photothermal and photodynamic therapy. We believe that the low-temperature synthetic method introduced here might offer a general way of crystalline deposition of TiO(2 )on a variety of gold nanostructures, broadening the spectrum of NIR-responsive photocatalytic hybrid nanostructures for biomedical applications. (C) 2022 Published by Elsevier Ltd.